Myotropic Activities of Tick Pyrokinin Neuropeptides and Analog in Feeding Tissues of Hard Ticks (Ixodidae) - Xiong, Caixing; Wulff, Juan P.; Nachman, Ronald J.; Pietrantonio, Patricia V. (Frontiers in Physiology, 2022)
Neuropeptides regulate many important physiological processes in animals. The G protein-coupled receptors of corresponding small neuropeptide ligands are considered promising targets for controlling arthropod pests. Pyrokinins (PKs) are pleiotropic neuropeptides that in some insect species stimulate muscle contraction, and modulate pheromone biosynthesis, embryonic diapause, and feeding behavior. However, their function remains unknown in ticks. Here, we report the myotropic activity of tick endogenous PKs and a PK agonist analog, PK-PEG8 (MS[PEG8]-YFTPRLa), on feeding tissues of two tick species representing the family Ixodidae lineages: Prostriata (Ixodes scapularis) and Metastriata (Rhipicephalus sanguineus). First, we predicted the sequences of two periviscerokinins (PVK), one with a derived ending RNa, and five PKs encoded by the CAPA peptide precursor from R. sanguineus and found the encoded PKs were identical to those of R. microplus identified previously. The pharynx-esophagus of both tick species responded with increased contractions to 10 µM of the endogenous PK as well as to PK-PEG8 but not to the scrambled PK peptide, as expected. A dose-dependent myotropic activity of the PK-PEG8 was found for both tick species, validating the analog activity previously found in the pyrokinin recombinant receptor assay. In agreement with the tissue activity elicited, we quantified the relative transcript abundance of R. sanguineus PK receptor in unfed female ticks and found it was the highest in the feeding tissues extracted from the capitulum, and lowest in the reproductive tissue. This is the first report of the activity of pyrokinins in ticks. These findings strongly indicate the potential role of PKs in regulating tick blood feeding, and therefore, making the tick PK receptor a potential target for interference.